ASCORBIC ACID AS A GROWTH ADJUVANT IN ENCAPSULATED PROTOCORM-LIKE-BODIES OF RHYNCHOSTYLIS RETUSA BL. (ORCHIDACEAE) - Sembi, Jaspreet K.; Kahlon, Parvinderdeep S.; Kalsotra, Tania; Sidhu, Sukhjeet Kaur (Current Botany, 2017)
In the present study, effect of ascorbic acid, a known growth adjuvant on encapsulated protocorm-like-bodies (PLBs) of Rhynchostylis retusa Bl. was investigated. PLBs were encapsulated in calcium alginate (3.5% sodium alginate and 100mM calcium chloride) prepared in Mitra et al. (1976) basal medium and supplemented with different concentration of ascorbic acid (5, 10, 15, 20mM). The encapsulated PLBs were stored at 25Â°C. Their germination response and germination potential was evaluated after every 4 weeks on basal media. Control set of encapsulated PLBs, failed to germinate after 32 weeks. However, PLBs with 15mM ascorbic acid in the encapsulated matrix showed the best response; nearly 90% germinated even after 32 weeks of storage. The survival and germination frequency was directly proportional to the level of ascorbic acid in the alginate mix upto 15mM level but declined on further increase. Differentiation of PLBs into plantlet was better in synthetic seeds containing lower concentration of ascorbic acid (5mM) as compared to higher levels (15, 20mM) whereas multiplication of secondary PLBs was more pronounced at higher levels. Chlorophyll content was inversely proportional to the level of ascorbic acid in the nutrient mix; lush green PLBs were observed at low concentration of ascorbic acid (5mM). This study highlights the potential of ascorbic acid as an aid to growth and survival of encapsulated PLBs upon storage.